PR ACTIVITIES AT THE ENREKANG DISTRICT DPRD SECRETARIAT OFFICE IN PUBLICATION OF LEGISLATIVE MEMBERS' CONSTITUENT VISITS (Karya Ilmiah Mahasiswa (KIMA), 2024)
This study aims to determine public relations activities at the secretariat office of the DPRD of Enrekang Regency in the publication of constituent visits by members of the legislature. The research technique used is qualitative research. Data collection techniques with data analysis using a cycle model. Data collection was carried out by observation, interviews and documentation techniques. Analysis of the research data uses three components consisting of data reduction, presentation, and drawing conclusions. The results showed that the public relations activities of the Enrekang Regency DPRD secretariat included many things, one of which was as a provider of publications for visiting constituents of the legislature, public relations activities consisted of non-physical and physical which included taking publication materials and then process them into appropriate information for the community. Public relations activity in the publication of work visits is only one of the many activities carried out by public relations, while the implementation of publications given by public relations this implementation is nothing but an activity and action carried out by public relations in publications during working visits carried out by members of the Enrekang Regency legislature. In addition to the form of implementing the role of communication for the continuity of activities, in this case, publication is also very important. Implementation of public relations in providing information not only as a provider but also makes the community as a supervisor of the work of members of the legislature who are given the mandate by the community.